Evasion of Apoptosis as a Cellular Stress Response in Cancer - Simone Fulda (International Journal of Cell Biology)
One of the hallmarks of human cancers is the intrinsic or acquired resistance to apoptosis. Evasion of apoptosis can be part of a cellular stress response to ensure the cell's survival upon exposure to stressful stimuli. Apoptosis resistance may contribute to carcinogenesis, tumor progression, and also treatment resistance, since most current anticancer therapies including chemotherapy as well as radio- and immunotherapies primarily act by activating cell death pathways including apoptosis in cancer cells. Hence, a better understanding of the molecular mechanisms regarding how cellular stress stimuli trigger antiapoptotic mechanisms and how this contributes to tumor resistance to apoptotic cell death is expected to provide the basis for a rational approach to overcome apoptosis resistance mechanisms in cancers.